The effects of corporate governance on environmental sustainability reporting: empirical evidence from South Asian countries - Md. Abdul Kaium Masud; Mohammad Nurunnabi; Seong Mi Bae (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2018)
Comparatively less research has examined the effect of corporate governance (CG) elements on environmental sustainability reporting performance (ESRP) in South Asian (SA) countries. Further, no study in literature documents a cross-country examination of CG and ESRP in this region. The study takes three SA countries (Bangladesh, India, and Pakistan) and 88 listed organizations' sustainability reports during the years 2009-2016 from the Global Reporting Initiative (GRI) database. The study considers a variety of mixed theoretical frameworks-i.e., agency, resource dependency, stakeholder, legitimacy and political cost theories-to indicate which ownership (foreign, institutional, director and family) and board characteristics (independence, size, diversity and committee) affect ESRP practices in the world's most environmentally vulnerable region. Our empirical results indicate ESRP has a positive association with foreign and institutional ownership, board independence, and board size. Moreover, we find director share ownership significantly relates with ESRP. In contrast, our results also reveal no association between ESRP and family ownership, female directorship, and CSR and environmental committees. We conclude that more family control, a lack of female participation, and the unavailability of resourceful management personnel primarily impedes ESRP practices in the SA countries' organizations. These findings have both theoretical and practical implications for academia, policy-makers, and corporate managers in this region.
Keywords: 650; Environmental sustainability reporting; Corporate governance; South Asia; Bangladesh; India; Pakistan; Disclosure; GRI